2015
DOI: 10.1155/2015/138073
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Utilization of Traditional Medicine among the Communities of Merawi Town, Northwest Ethiopia: A Cross-Sectional Study

Abstract: Background. In Ethiopia, up to 80% of the population use traditional medicine for primary health care. Studies on the current knowledge and practices of communities in the era of modern health care expansion are lacking. Therefore, this study is aimed at assessing the knowledge, attitude, and practice of traditional medicine among communities in Merawi town. Methods. A descriptive cross-sectional study was carried out among 403 residents of Merawi town. A systematic random sampling was used to select household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 8 publications
12
67
4
4
Order By: Relevance
“…However, the observed magnitude of herbal medicine use in this study was greater than the research findings in Kenya (12%) [8] and Italy (27.8%) [41]. The common practice of herbal medicine in the current study can be explained in part by the fact that tradition and culture in Ethiopia promote the use of herbal medicines which is further reinforced by the presence of many traditional medicinal practitioners [42,43]. Differences in study design, population sampling and ethnicity may also lead to discrepancies in prevalence rates in the above studies compared to the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…However, the observed magnitude of herbal medicine use in this study was greater than the research findings in Kenya (12%) [8] and Italy (27.8%) [41]. The common practice of herbal medicine in the current study can be explained in part by the fact that tradition and culture in Ethiopia promote the use of herbal medicines which is further reinforced by the presence of many traditional medicinal practitioners [42,43]. Differences in study design, population sampling and ethnicity may also lead to discrepancies in prevalence rates in the above studies compared to the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…Difference were observed in women age averagely that explained young and old women included in this study and could be seen as a good representative sample [21]. Study done by Author Wassie S, et al [22] in Ethiopia revealed that 70% of participants didn't agree the effectiveness of traditional medicine that was confirmed also in this study i.e. women were preferred modern medicine for cervical cancer treatment.…”
Section: Discussionsupporting
confidence: 66%
“…The evidences for use of herbal drugs in various societies is ample, these traditional health care systems have been used in nursing numerous ailments even without the proper awareness of their ingredients and precise role (Patel et al 2012). The inflated use of traditional medicine is attributed to their wide social and cultural acceptance, as alternative remedial approaches have been about for centuries (Wassie et al 2015). In addition, these herbal remedies are also affordable to all population in comparison to costly allopathic medicine (Maroyi, 2013).…”
Section: Accessible and Affordablementioning
confidence: 99%